Independent Risk Factors for RBC Transfusion in Children Undergoing Surgery. Analysis of 14,248 Cases at a German University Hospital - Florian Piekarski; Vanessa Neef; Patrick Meybohm; Udo Rolle; Wilfried Schneider; Kai Zacharowski; Elke Schmitt (MDPI AG, 2021)
Background: paediatric patients are vulnerable to blood loss and even a small loss of blood can be associated with severe shock. In emergency situations, a red blood cell (RBC) transfusion may become unavoidable, although it is associated with various risks. The aim of this trial was to identify independent risk factors for perioperative RBC transfusion in children undergoing surgery. Methods: to identify independent risk factors for perioperative RBC transfusion in children undergoing surgery and to access RBC transfusion rates and in-hospital outcomes (e.g., length of stay, mortality, and typical postoperative complication rates), a monocentric, retrospective, and observational study was conducted. Descriptive, univariate, and multivariate analyses were performed. Results: between 1 January 2010 and 31 December 2019, data from n = 14,248 cases were identified at the centre. Analysis revealed an RBC transfusion rate of 10.1% (n = 1439) in the entire cohort. The independent predictors of RBC transfusion were the presence of preoperative anaemia (p < 0.001; OR = 15.10 with preoperative anaemia and OR = 2.40 without preoperative anaemia), younger age (p < 0.001; ORs between 0.14 and 0.28 for children older than 0 years), female gender (p = 0.036; OR = 1.19 compared to male gender), certain types of surgery (e.g., neuro surgery (p < 0.001; OR = 10.14), vascular surgery (p < 0.001; OR = 9.93), cardiac surgery (p < 0.001; OR = 4.79), gynaecology (p = 0.014; OR = 3.64), visceral surgery (p < 0.001; OR = 2.48), and the presence of postoperative complications (e.g., sepsis (p < 0.001; OR = 10.16), respiratory dysfunction (p < 0.001; OR = 7.56), cardiovascular dysfunction (p < 0.001; OR = 4.68), neurological dysfunction (p = 0.029; OR = 1.77), and renal dysfunction (p < 0.001; OR = 16.17)). Conclusion: preoperative anaemia, younger age, female gender, certain types of surgery, and postoperative complications are independent predictors for RBC transfusion in children undergoing surgery. Future prospective studies are urgently required to identify, in detail, the potential risk factors and impact of RBC transfusion in children.